(untitled) (Research, Society and Development, 2022)
Atopic dermatitis (AD) is a chronic and recurrent inflammatory skin disease that could be associated with cardiovascular diseases (CVDs). Interest in determining whether the chronic inflammation of AD is a risk factor for CVD has been growing in recent years, although there are few studies available on this topic, and the results are quite controversial. The purpose of this scoping review was to understand whether severe atopic dermatitis and its chronic systemic inflammatory process contribute, or not, as a risk factor for the development of CVD. Following the development of a study protocol, a scoping review was carried out based on the structure outlined by Arksey and O’Malley, Levac et al., the Joanna Briggs Institute and the PRISMA-ScR guidelines. PubMed, Cochrane, EMBASE, CINAHL, LILACS, Web of Science, Biblioteca Virtual em Saúde (BVS), Scopus and SciELO were the selected databases. Results: Fifty-two studies were included in this review (18 review studies, 16 cross-sectional studies, 15 cohort studies and three meta-analyses). We found that 36 studies could associate AD with CVD, while 16 studies found no relationship between AD and CVD. Conclusions: It is possible that cardiovascular risk in moderate to severe atopic disease is in confounding factors, and not necessarily because AD and CVDs share the same chronic systemic inflammatory pathway. There is no robust evidence that AD is a risk factor for CVD. To reduce CVD risk in patients with AD, we must pay attention to the risk factors commonly present in these patients and strongly recommend a healthy lifestyle.